Information doesn't want to be free laws for the internet age - Doctorow, Cory 1971-; Palmer, Amanda 1976-; Gaiman, Neil 1960- (McSweeney's, 2014)
Information Doesn't Want to Be Free takes on the state of copyright and creative success in the digital age. Can small artists still thrive in the Internet era? Can giant record labels avoid alienating their audiences? This is a book about the pitfalls and the opportunities that creative industries (and individuals) are confronting today ... about how the old models have failed or found new footing, and about what might soon replace them. Information Doesn't Want to Be Free offers a guide to the ways creativity and the Internet interact today, and to what might be coming next